What is the requirement for out-of-hours operating in orthopaedics?. Issue 2 (June 1993) - McKee, M; Priest, P; Ginzler, M; Black, N
Abstract : Recent reports have emphasized the need to reduce the amount of unsupervised surgery performed at night by junior doctors. However there is little guidance about when an operation must be performed urgently and when it can be postponed safely. This study describes the existing pattern of out-of-hours trauma and orthopaedic surgery in four hospitals and reports the views of a panel of surgeons and anaesthetists on the extent to which operating could be postponed until the following day. Operations at night are uncommon--a mean of 0.6 per night and occurring on only 40% of nights--though their frequency shows two-fold variation between hospitals. With certain assumptions it is estimated that up to a third of out-of-hours operations could be postponed safely to the following day. Further evaluation is required of those operations about which the panel failed to reach agreement. While most of the procedures undertaken at night are within the competence of a registrar, some require the direct involvement of a consultant.